Future research and innovation priorities in the field of natural hazards, disaster risk reduction, disaster risk management and climate change adaptation: a shared vision from the ESPREssO project. (December 2020) - Zuccaro, G.; Leone, M.F.; Martucci, C.
Abstract: The H2020 ESPREssO project (Enhancing Synergies for Disaster Prevention in the European Union), aimed at identifying the existing gaps and key priorities for Research and Innovation (R&I) in the domains of Natural Hazards (NH), Disaster Risk Reduction (DRR), Disaster Risk Management (DRM) and Climate Change Adaptation (CCA). Key research priorities have been framed within the Sendai Framework for Disaster Risk Reduction 2015–2030 (SFDRR) and the related EU Action Plan, exploring the opportunities emerging from the linkages with the Sendai priorities and the key overarching issues from the literature review and networking activities carried out by ESPREssO project. The many ongoing initiatives at European and Global levels on NH, DRR, DRM and CCA and have been taken into account, with the aim of providing a harmonised framework able to capture the complexity of these fields, in terms of research and innovation and deliver a synthesized view of the emerging priorities. The paper identifies five broad areas of R&I in the field of DRR and CCA where EU investment is needed, highlighting for each of them relevant key topics of investigation. These areas (Improved Risk and Impact Assessment; Better Data for Resilient Future; Risk Governance and Partnership; Overcoming the Implementation Gap in DRR and CCA; Human Behaviour and Disaster Risk) have been suggested by the ESPREssO "Vision Paper" [1] as an answer to the relevant gaps and needs as expressed by the network of stakeholders and international experts engaged during the project. The Vision Paper is available at http://www.espressoproject.eu/images/deliverables/ESPREssO_D5.5.pdf .